A travel cost analysis of elk-viewing opportunity generated from an elk reintroduction project in Tennessee. Issue 1 (2nd January 2022) - Chapagain, Binod P.; Poudyal, Neelam C.; Watkins, Cristina
ABSTRACT: Long-term success of wildlife restoration programs depends on their potential to bring economic benefits to stakeholders. Because of the non-market nature of some benefits (e.g., wildlife viewing), however, demonstrating the economic value of such programs is often challenging. By employing a travel cost model of elk-viewing trips among households around the North Cumberland Wildlife Management Area, Tennessee, this study estimated the net economic benefit of elk-viewing opportunities generated from an elk reintroduction program. Depending on the assumptions about visitors' opportunity cost of time, the net economic benefit of elk viewing was estimated to range from 21/trip to 53/trip. When aggregated across the population, the total economic value of the elk-viewing opportunity generated from this restoration program was estimated to be as high as 6.95 million. Results from this study will be useful in characterizing the economic benefits of elk viewing and providing economic justification for restoration programs.